Aspek Hukum Pidana Dampak Penyalahgunaan Narkotika Bagi Remaja - July Esther; Herlina Manullang; Debora; Arismani (Jurnal Visi Pengabdian Kepada Masyarakat, 2021)
This outreach activity aims to increase knowledge about the criminal law aspects of the impact of narcotics abuse and increase the experience of communicating and interacting with the community directly through this community service activity. This training is conducted offline. Participants are 40 Youth Church of HKBP Sidorame Medan. The implementation is opening, counseling, video screening, presentation of posters on the impact of narcotics abuse, question and answer sessions, and participant feedback. Participants were enthusiastic about this activity, as seen from the participants' feedback. As many as 80 % of participants thought this extension went very well and all participants agreed that this activity was very useful Counseling delivered according to the needs of participants, invites all parties including parents, teachers, and the community to take an active role in being aware of the threat of narcotics to the younger generation. There are many things that can still be done to prevent teenagers from abusing narcotics, and to help teenagers who have fallen into drug abuse